Optimal synthesis of periodic sorption enhanced reaction processes with application to hydrogen production. (12th July 2018) - Arora, Akhil; Bajaj, Ishan; Iyer, Shachit S.; Hasan, M.M. Faruque
Highlights: Systematic design and synthesis framework for multi-step, multi-mode and periodic sorption-enhanced reaction processes (SERP). Simultaneous selection of optimal SERP cycle configurations, design specifications and operating conditions. Generalized boundary condition formulation and a continuous representation for the selection of discrete operation modes and flow directions. Simulation-based constrained grey-box optimization strategy to obtain optimal SERP cycles and design parameters. Novel cyclic SE-SMR process that obtains 95% pure hydrogen from natural gas with 35% higher productivity and 10.86% lower cost than existing processes. Graphical abstract: Abstract: A systematic design and synthesis framework for multi-step, multi-mode and periodic sorption-enhanced reaction processes (SERP) is presented. The formulated nonlinear algebraic and partial differential equation (NAPDE)-based model simultaneously identifies optimal SERP cycle configurations, design specifications and operating conditions. Key modeling contributions include a generalized boundary-condition formulation and a representation that enables the selection of discrete operation modes and flow directions using continuous pressure variables. A simulation-based constrained grey-box optimization strategy is employed to obtain optimal cycles and design parameters. The framework has been used for designing two SERP systems, namely sorption-enhanced steam methane reforming (SE-SMR) and sorption-enhanced water gas shift reaction (SE-WGSR), for maximizing hydrogen productivity and minimizing hydrogen-production cost. Specifically, a cyclic SE-SMR process is designed that obtains 95% pure hydrogen from natural gas with 35% higher productivity and 10.86% lower cost compared to existing small-scale, distributed systems. The developed synthesis framework can also be applied for other applications.